2019
DOI: 10.1021/acssynbio.8b00519
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosing Escherichia coli as a Whole-Cell Biocatalyst of Fatty Acids

Abstract: Whole cell biocatalysts can be used to convert fatty acids into various value-added products. However, fatty acid transport across cellular membranes into the cytosol of microbial cells limits substrate availability and impairs membrane integrity, which in turn decreases cell viability and bioconversion activity. Because these problems are associated with the mechanism of fatty acid transport through membranes, a wholecell biocatalyst that can form caveolae-like structures was generated to promote substrate en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Finally, in another study, FadL was overexpressed in a strain expressing human Cav1 proteins (Shin et al, 2019). Cav1 proteins stimulate the formation of endosomes that excise from the inner membrane.…”
Section: Engineering the Fatty Acid Import System Of E Coli For Biotechnological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in another study, FadL was overexpressed in a strain expressing human Cav1 proteins (Shin et al, 2019). Cav1 proteins stimulate the formation of endosomes that excise from the inner membrane.…”
Section: Engineering the Fatty Acid Import System Of E Coli For Biotechnological Applicationsmentioning
confidence: 99%
“…This study also observed negative effects on overall productivity after a stronger overexpression of FadL, further demonstrating the importance of fine‐tuning the expression of transporters to avoid membrane stress. Finally, in another study, FadL was overexpressed in a strain expressing human Cav1 proteins (Shin et al, 2019). Cav1 proteins stimulate the formation of endosomes that excise from the inner membrane.…”
Section: Fatty Acid Transport In Bacteriamentioning
confidence: 99%
“…Cav1 has also been employed to increase the accumulation of membrane proteins in E. coli [ 21 ] or to enhance the uptake and conversion of fatty acids into esters. [ 22 ] We thus examined whether the production of rainbow colorants can be enhanced by expanding membrane structures by generation of IMVs through employing caveolae.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies attempted to resolve this issue by membrane engineering [17] such as increasing the membrane area [18,19] or by forming intracellular lipid droplets which can serve as an intracellular reservoir for hydrophobic compounds. [20] Although there have been preliminary reports on employing morphology engineering and formation of inner-membrane vesicles (IMVs) or outer-membrane vesicles (OMVs) for enhancing the production of hydrophobic compounds, [18][19][20][21][22][23] combinatorial applications of these membrane engineering strategies have not been reported. Despite these attempts, the titers of natural colorants need to be further increased for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxicity has been closely associated with reduced metabolic activity, due to substrate or product inhibition. To overcome this issue, several strategies have been developed, such as adding adsorbent resin, 16 forming caveolae, 32 and modifying the membrane structure. Instead, this study employed laboratory adaptive evolution to improve cell tolerance toward elevated FAs concentrations.…”
Section: ■ Discussionmentioning
confidence: 99%